Problems that the students face while solving 1st Degree Equations with two Unknown, during their prepare to the High School Entrance Exam (SBS) - Burhanzade, Hulya; Aygor, Nilgin (ELSEVIER SCIENCE BV, 2014)
The purpose of the research is identified and manufactures a solution to the problems of the students who attended the High-School Exam (SBS) while solving the 1st Degree Equations with two unknown. Sample of the research is 30 students from 2 different schools in 8th grade of the 2011-2012 academic years in Fahir Ilkel Primary School and Inonu Primary school. The study used both qualitative and quantitative methods. To gather the results of the research, three verbal and three numerical, in total 6 classical methods, questions are given. The data was analyzed by researchers jointly. After analyzing the results we discovered that some of the problems the students face are; calculation errors, students cannot remember the subjects efficiently, lack of information about the related subject, ability to solve test method rather than classical method questions and to establish the relationship between them because of summarize without understanding the conceptual and operational knowledge. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: High School Entrance Exam-(SBS); 1st Degree Equations; the success of solving equations; mathematics education; Education & Educational Research; Social Sciences - Other Topics